THE APPLICATION OF SERVANT LEADERSHIP IN BUILDING CREATIVITY IN TOURISM START-UP TEAM IN SURABAYA - Agoes Tinus Lis Indrianto; Tony Antonio; Liestya Padmawidjaja (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Creativity is one of the most important personalities that has to be possessed by of start-up team. It is considered as the crucial step that lead to innovation process. In this case, creative team will open more possibility for the team to be successful in their projects. As one of the industries that heavily affected in digital technology, tourism need new ideas and ne business model to develop. This opens many opportunities in building tourism start-up in the areas of goods or services. As the second biggest city in Indonesia, the city of Surabaya also become the home of many start up teams, including in tourism sector. In building team creativity, the role of team leaders is important to lead and empower the team. One of the concepts of leadership that has been known to be effective is servant leadership. The application of servant leadership in a team can give space for the member to be more creative and innovative. This study focuses on the application of servant leadership in building team creativity. The study describes and analyze the impact servant leadership that has been applied to tourism start up team in Surabaya. The leader characters and the way they practice servant leadership are being discussed. This is a qualitative study that use the leaders of start-ups tourism team from Surabaya as the respondents. The teams that are chosen consist of mostly young people in the areas of tourism, hospitality and culinary. In-depth interview with the team leaders, observation on the team activities and publication review are conducted to collect data for the study. The collected data is analyzed using manual data analysis method, through data selection and categorization. The study show that servant leadership application can be seen in three phases, namely idea generation, problem solving and target achievement. There are several attributes of servant leadership that have been practiced to boost team creativity. The data is presented narratively and the result shows indicate that the application of servant leadership has great impact on team creativity.